Pelatihan Penggunaan Komputer dan Instalasi Hardware Komputer Pada Praktek Mandiri Bidan Supiani Dalam Mendukung Peningkatan Pelayanan - Budi Triandi; Iwan Fitrianto Rahmad; Ratih Puspasari; Lili Tanti; Bob Subahan Riza; M Rizky (Journal of Social Responsibility Projects by Higher Education Forum, 2022)
The practice of Mandiri Midwife Supiani is a maternity clinic where service and marketing operations still use conventional methods, the founder of the Mandiri Midwife Supiani practice took the initiative to establish services for public health, especially for services for pregnant women and childbirth based on health services which is the most important thing for the community, where the community will consult and brobat for the complaints suffered against him. But if it is not supported by information technology, this noble idea will sink and become obsolete by the trend of the development of people's habits in obtaining information, where currently social media plays an important role in the marketing field, excellent service will be realized by the application of information technology, based on this the team provide solutions and assist the founder and owner of the Mandiri Midwife Supiani practice to be able to realize the application of Information technology as an excellent service supporter, with the stages of conducting training on how to use computers and helping to install computer networks so that the system can synergize in providing excellent service to the community, with the aim of improve the quality of health services in an excellent manner with the application of information technology. This paper reports on the activities during which the team carried out PKM at the Supiani Midwife's Independent Practice. After the training for partners, namely independent midwives, supine experienced an increase of 97.78% in terms of skills and understanding of the use of information technology in supporting service performance for patients